HIV Related stigma and discrimination interventions among adolescents and young people 15-24 years living with HIV in Busia HCIV. - Nekesa, Gertrude; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David (Student's Journal of Health Research Africa, 2025)
Introduction The UNAIDS global estimates show that about 4400 new HIV infections occur among people aged between 15 and 24 years, of whom almost 43% are among young women. Goal To reduce all forms of HIV related stigma and discrimination among adolescents and young people (15-24 years) living with and affected by HIV in Busia HCIV by 70% in 12 months Project design The project was based on an evidence-based needs assessment that utilized the key informant approach and a root cause analysis that identified the need for a change in reducing HIV stigma and discrimination among adolescents and young people living with and affected by HIV/AIDs in Busia HCIV ART clinic. The intervention approach was based on the ADKAR theory of change, John Kotter’s 8-step theory of change, incorporating the theory of reasoned action, the health belief model, adult learning theory, and the social cognitive theory. The project also examined the influence of leadership, power, culture, and policies on the change process. Project outcomes The project is still ongoing; however, the mid-evaluation that was done quarterly showed improving retention and disclosure of HIV status among adolescents and young people. There was also significant evidence of reduced stigma and discrimination at the facility and in the community, as seen by the social support provided by family members, and the high self-esteem and confidence among adolescents and young people, leading to improved quality of care. Recommendation Sensitization campaigns should be beefed up among Health workers, community leaders, and other stakeholders to address potential causes and sources of stigma among people living with and affected by HIV.